Environmental geological features of the red clay surrounding rock deformation under the influence of rock-fracture water - Wang, Jiading; Gu, Tianfeng; Wang, Jianbin; Xu, Yuanjun; Chen, Peng; Muhammad Aqeel Ashraf (Penerbit Universiti Kebangsaan Malaysia, 2017)
The development degree of fissure water in underground rock is a great trouble to the construction of railway tunnel, which will cause a series of environmental geological problems. Take the surrounding rock-section of the typical red clay in Lvliang-Mt. railway tunnel below the underground water level as an example, several aspects about the red clay surrounding rock will be researched, including pore water pressure, volume moisture content, stress of surrounding rock, vault subsidence and horizontal convergence through the field monitoring. Taking into account the importance of railway tunnel engineering, the large shear test of red clay was carried out at the construction site specially and the reliable situ shear strength parameters of surrounding rock will be obtained. These investigations and field tests helped to do a series of work: Three dimensional finite element numerical model of railway tunnel will be established, the deformation law of the red clay surrounding rock will be investigated, respectively, for the water-stress coupling effect and without considering it, the variation of the pore water pressure during excavation, the influence degree about the displacement field and stress field of water-stress coupling on red clay-rock will be discussed and the mechanism of the surrounding rock deformation will be submitted. Finally, the paper puts forward the feasible drainage scheme of the surrounding rock and the tunnel cathode. The geological environment safety of tunnel construction is effectively protected.